The enhancement of immunoactivity induced by immunogenic cell death through serine/threonine kinase 10 inhibition: a potential therapeutic strategy - Xia, Xiaoli; Wang, Yixin; Wang, Minghui; Lin, Jian; Wang, Ruiheng; Xie, Shufeng; Yu, Yaoyifu; Long, Jinlan; Huang, Zixuan; Xian, Huajian; Zhang, Wenjie; Lu, Chaoqun; et al. (Frontiers in Immunology, 2024)
Introduction Immunogenic cell death (ICD) is capable of activating the anti-tumor immune response of the organism; however, it is concurrently a complex process involving multiple factors. The specific factors that impact the occurrence of ICD remain undefined. Methods Through cluster analysis, patient specimens retrieved from the TARGET, TCGA, and GEO AML databases were categorized into two subtypes based on the expression levels of ICD-related genes: ICD-high and ICD-low. We compared the prognostic survival outcomes, pathway enrichment analysis, and immune cell infiltration between these two subtypes. Additionally, we identified factors related to AML development from multiple databases and verified the role of these factors both in vivo and in vitro in activating the immune response during the occurrence of ICD. Results and discussion In the ICD-high subtype, there was a notable increase in the abundance of immune cell populations, along with the enrichment of pathways pertinent to the activation of various immune cells. Despite these immunological enhancements, this subgroup demonstrated a poorer prognosis. This phenomenon was consistently observed across various additional AML datasets, leading us to hypothesize that elevated expression of ICD genes does not invariably correlate with a favorable prognosis. Notably, STK10 exhibited elevated expression in AML, was associated with a poor prognosis, and showed synchronous expression patterns with ICD genes. Inhibition of STK10 led to the activation of ICD and the induction of an antitumor response. Moreover, when combined with other ICD inducers, it produced a synergistic anti-tumor effect. Our results reveal the impact of STK10 on ICD and underscore its key role in initiating ICD.